Upaya Meningkatkan Hasil Belajar Peserta Didik Dengan Menggunakan Pendekatan TPACK Kelas II SDN 16 Mataram Tahun Pelajaran 2022/2023 - Susanti, Yusi; Mahardhika, Deni Tri Agus; Istinigsih, Siti (Journal of Science Instruction and Technology, 2023)
This research aims to improve student learning outcomes by using the TPACK approach for class II SDN 16 Mataram, totaling 28 students. This type of research is collaborative classroom action research. The data collection techniques used in this research were test, observation and documentation. The results of the research show that there is an increase in student learning outcomes and student activity. In the pre-cycle stage, learning outcomes and observations of student learning activities were found to be 46% and 50% respectively with the Fairly Good (C) category, while at the cycle 1 respectively obtained 64% and 69% in the Good (B) category, and in cycle 2 each obtained 82% and 80% in the Very Good (SB) category. Thus, it can be concluded that the TPACK approach can improve the learning outcomes of class II students at SDN 16 Mataram.